Pengaruh Perputaran Piutang terhadap Return On Asset pada Usaha Nani Collection Sibolga - Ade Septia Parawansah; Yusi Tri Utari Panggabean (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to determine the effect of accounts receivable turnover on Return on Assets (ROA) at Nani Collection Sibolga for the 2020–2024 period. This research employed a quantitative approach using a descriptive associative method. The data used were secondary data in the form of financial statements consisting of balance sheets and income statements for five years. The data analysis techniques included classical assumption tests, correlation analysis, coefficient of determination, simple linear regression, and hypothesis testing using SPSS software. The results of the study indicate that accounts receivable turnover has a positive and significant effect on Return on Assets at Nani Collection Sibolga. This finding shows that the higher the accounts receivable turnover, the higher the company’s ability to generate profit through the utilization of its assets. Effective receivables management can help improve cash flow and company profitability.